Inovasi dalam Perencanaan Sumber Daya Manusia pada Lembaga Pendidikan Islam - Kurnia, Dela; Fronica, Imelda; Simamora, Rosmailani; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine human resource planning (HR) and innovation in human resource planning (HR). This type of research uses qualitative research methods. The process of obtaining data is carried out by finding sources and constructing them from various sources such as books, journals/articles and research that has been carried out previously. Based on research, it shows that human resource planning is a function that must first be implemented in an organization. HR Planning is a management process in determining the movement of an organization's HR from its current position to its desired position in the future. An institution must innovate in Human Resource planning, the innovations that can be implemented are, Human Resource Analytics, Artificial Intelligence in Recruitment, Use of Big Data, Machine Learning for Employees, Employee Sentiment Analysis, Virtual (VR) and Augmented Human Resources Reality (AR), Work Flexibility, Work-Based Promotion, Improved Work-Life Balance, Partnership with Education, experience and Performance-based Compensation, Use of Mobile Applications and Gamification